FROM THE GUANO WAR TO THE GODO WAR. CONDITIONS, OBJECTIVES AND NATIONALIST DISCOURSE IN THE SPANISH CONFLICT WITH PERU AND CHILE (1862-1867). - Inarejos Muñoz, Juan Antonio (Revista de Historia Social y de las Mentalidades, 2024)
From a general perspective the Spanish  international interventions in the wars against  Peru and Chile during the “bajoisabelino”  period have been described as a part of  a romantic and undefined foreign policy.  Nevertheless this paper tries to refute this  interpretative paradigm and to analyse the  main reasons of the conflict and its impact  in the articulation of nationalist rhetoric.  Along this line, it also studies the leading  role of the domestic policy and the public  opinion to guide the foreign policy. Finally,  this approach shed light into the research  on international relations in two important  topics, the relations between Spain and its  former colonies and the European strategies  aimed to contain and to face the United States  Monroe’s doctrine.
Keywords: Elizabeth the second Kingdom; Spanish Foreign Policy; nationalism rhetoric